ANALISIS PENGGUNAAN WORDWALL SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS II SEKOLAH DASAR - Rahardian Adi Nugroho; Tri Joko Raharjo; Eko Handoyo; Sri Sumartiningsih; Agus Yuwono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyse the use of the Wordwall platform as an interactive learning media in increasing the motivation to learn mathematics of grade II students at SDN Sungai Bambu 01. In the era of the Industrial Revolution 4.0, technological advances have a major impact on various aspects, including education, which requires educators to take advantage of technology in learning. Interesting and interactive media is proven to help overcome common problems in education, namely low student interest and motivation to learn, especially in mathematics lessons which are often considered monotonous. This research uses descriptive qualitative method with data collection techniques such as observation, questionnaire, and literature study to obtain data related to the effectiveness of Wordwall. The results show that Wordwall is able to increase students' participation and motivation to learn, which can be seen from their activeness, enthusiasm, and courage to ask questions and actively participate in the learning process. By using Wordwall media, the learning environment becomes more dynamic, fun and conducive, thus contributing positively to students' understanding and interest in mathematics materials. This research contributes to the development of technology-based learning media and suggests educators to integrate Wordwall in learning activities to improve the effectiveness and efficiency of the teaching-learning process.